Platelets reactivity as a predictor of the extent of myocardial infarct damage and poor outcomes in STEMI patients undergoing primary PCI. (25th November 2020) - Massalha, E; Goitein, O; Fardman, A; Grupper, A; Mazin, I; Natanzon, S; Beigel, R; Matetsky, S
Abstract: Background: Despite optimized management of STEMI patients including primary PCI (PPCI) and use of novel anti-platelet agents, a substantial proportion still display a large infarct size and microvascular damage. The extent of MI and presence of microvascular damage as determined by cardiac MRI (CMR) are considered as powerful prognostic factors in predicting both early and long-term prognosis in those patients. Platelets reactivity has been implicated in pathogenesis of microvascular and subsequent myocardial damage including distal embolization, microvascular platelets plugging and inflammation. Methods: We prospectively evaluated 105 consecutive STEMI patients, with no prior MI, who underwent PPCI. Patients underwent 2D-echocardiography within 48 hours of admission and cardiac MRI (CMR) 5±1 day post admission. All Patients were treated with dual antiplatelet agents and blood sample were analyzed for platelets reactivity (PA) at 72 hours post admission, using arachidonic acid (AA) and adenosine diphosphate (ADP) as agonists. Aspirin hypo-responsiveness was defined as AA-PA≥30%, and P2Y12 non-responsiveness as ADP-PA ≥50%. CMR was evaluated for late gadolinium enhancement (LGE) and microvascular obstruction (MVO), which reflects MI size and microvascular damage respectively. Both parameters were quantified as % of the LV mass. Major adverse cardiac events (MACE) were defined as the composite of death, MI, stroke, urgent revascularization and hospitalization due to either heart failure or bleeding during the first year post AMI. Results: AA and ADP inhibition were 22±17, and 34±16 respectively. Aspirin hypo-responsiveness was associated with significantly higher extent of LGE (p=0.04) and MVO (p=0.003). A multivariate logistic regression analysis revealed that AA-PA hypo-responsiveness is an independent predictor of both MI size as reflected in LGE (OR 3.87; 95% CI: 1.47–10.5, p=0.031), and higher extent of microvascular damage as reflected by MVO% of LV mass (OR 3.6; 95% CI: 1.15–10.3, p=0.027). Patients with aspirin hypo-responsiveness were significantly more likely to sustain MACE (36% vs 12%, HR 4.13, 95% CI: 1.52–10.2, p=0.003). As opposed to AA related platelets reactivity, no significant correlation was demonstrated between ADP induced platelets reactivity and either measures of MVO or LGE. Conclusions: In patients undergoing PPCI for STEMI, platelets reactivity in response to AA is an independent predictor of the extent of both myocardial and microvascular damage. Aspirin hypo-responsiveness is associated with higher rate of adverse events during 1-year follow-up. Funding Acknowledgement: Type of funding source: None